An iterative method for design of total water networks with multiple contaminants. (10th December 2019) - Fan, Xiao-Yan; Klemeš, Jiří Jaromír; Jia, Xuexiu; Liu, Zhi-Yong
Abstract: Compared to the synthesis of simple networks in which only reuse, regeneration reuse/recycling, or wastewater treatment is considered individually, the integration of total water networks is more complex and practical. This paper presents an iterative method for design of total water networks with multiple contaminants, in which reuse, regeneration reuse/recycling and wastewater treatment are considered simultaneously. To start the design procedure, an initial reuse-subnetwork without recycling streams is designed first. The un-reused streams in the initial reuse-subnetwork are employed to estimate the possible recycling streams by designing the treatment-subnetwork. Adding the possible recycling streams estimated into reuse-subnetwork as known source streams, the reuse-subnetwork with recycling streams can be designed. In the first iteration, the recycling streams, which will be reused in the reuse-subnetwork, will be identified from the possible recycling streams. With several iterations, the final design of the total water network can be obtained. The results obtained with the proposed method are comparable to that obtained in the literature with mathematical programming method. It is shown that the design procedure proposed is simple and effective. Highlights: Design method proposed for total water networks with multiple contaminants. Reuse, regeneration and wastewater treatment are considered simultaneously. An iterative design procedure is proposed. The final design can be obtained in a few iterations. The design procedure proposed is simple and effective.